Based on ADRC Strategy for Tracking Trajectory of Undamped Plants. Issue 1 (May 2021) - Hu, Weiwen; Zhang, Shengguo; Xu, Wenru; Yang, Jiawei; Hou, Hao
Abstract: This paper mainly actualizes the precise trajectory tracking for the direct-drive servo system with undamped plant. Using the nominal model of the undamped object in this paper is to realize the precise control and obtain the better tracking effects by adopting the ADRC strategy which is introduced to avoid the overshoot causing by design of typical PID control law and improve the robustness of servo system. Simultaneously, it can also achieve the fast tracking and obtain the better convergence effects. Extensive simulations indicate that it practically validates the superiority of adopting the ADRC strategy to control these typical undamped plant. Both average placement tracking error and velocity tracking error for the sinusoidal waves and multi-step signal are converging to the value fluctuating around zero or gradually approaching to zero. This all-around control strategy to achieve the precise and fast trajectory tracing for the direct-drive servo system with undamped object is effective and feasible.